The problem of constructing the diversification mechanisms of export potential of region - Кутідзе, Людмила Сергіївна (Technology audit and production reserves, 2015)
The formation and implementation of export potential is essential for Ukraine’s integration in the global space. Construction of the mechanisms of diversification of exports should be a priority for management export potential of the region, as well as diversification is one of the tools of risk prevention, reliability and stable functioning of the socio-economic system of the region. Therefore, an important issue is the identification and analysis of problems that prevent the construction of mechanisms to diversify the export sector in the region, and determining an acceptable solution. It is found that problems of development of diversification mechanisms lies in the fact that at the regional level is not formed responsible centers for development of export potential, not specified the mechanisms of interaction between government and business, there is no method of estimating the diversification of the export sector in the region that would become the basis for determining the directions of its development. Identification of these problems specifies directions for further theoretical and methodological works on construction of mechanisms to diversify the export potential of the region for further implementation in administrative practice.